2002
DOI: 10.1038/sj.onc.1205595
|View full text |Cite
|
Sign up to set email alerts
|

Decorin suppresses tumor cell-mediated angiogenesis

Abstract: The progressive growth of most neoplasms is dependent upon the establishment of new blood vessels, a process regulated by tumor-secreted factors and matrix proteins. We examined the in vitro and in vivo angiogenic ability of conditioned media obtained from fibrosarcoma, carcinoma, and osteosarcoma cells and their decorintransfected counterparts. Human endothelial cells were investigated in vitro by evaluating three essential steps of angiogenesis: migration, attachment, and differentiation. On the whole, wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
1
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 62 publications
7
178
1
3
Order By: Relevance
“…In contrast, decorin may also exhibit antiangiogenic effects under certain circumstances. [28][29][30][31][32] Clearly, further experiments are required to substantiate the role of decorin in adipose tissue angiogenesis. The effect of decorin deficiency on the vascularization of adipose depots in decorin-knockout mice fed a high-fat diet will be a key experiment in determining the role of decorin in obesity-associated angiogenesis within the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, decorin may also exhibit antiangiogenic effects under certain circumstances. [28][29][30][31][32] Clearly, further experiments are required to substantiate the role of decorin in adipose tissue angiogenesis. The effect of decorin deficiency on the vascularization of adipose depots in decorin-knockout mice fed a high-fat diet will be a key experiment in determining the role of decorin in obesity-associated angiogenesis within the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…27 DCN-EGFR interaction results in up-regulation of endogenous p21 expression and a concomitant suppression of human cancer cell line growth, angiogenesis and metastasis. [28][29][30] Given its established role as a suppressor of human tumorigenesis, it is possible that the proteoglycan also safeguards against endometrial cancer formation in the DES model. Additional studies to examine DCN levels in human endometrial carcinomas could shed light on DCN's role in endometrial cancers.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Overexpression of decorin inhibits TGF-b-induced proliferation and slows growth of a Chinese hamster ovary cell line. 4 In gene transfer studies of human colon cancer, cells stably transfected with decorin exhibited reduced growth rates in vitro and failed to generate tumors in severe combined immunodeficiency (SCID) mice.…”
Section: Ecorin Plays Different Roles In Regulating Matrixmentioning
confidence: 99%
“…12 Additionally, it has been indicated that decorin could adversely affect in vivo tumor growth by suppressing the endogenous tumor cell production of angiogenic stimulus. 3 Finally, it has been shown that ectopic expression of decorin in C6 rat glioma cells resulted in the inhibition of tumor formation in vivo. 13 These unique features make decorin a very good candidate gene for many experimental cancer gene therapy applications.…”
Section: Ecorin Plays Different Roles In Regulating Matrixmentioning
confidence: 99%
See 1 more Smart Citation